Simultaneous estimation of serum and cerebrospinal fluid adenosine deaminase level to differentiate tuberculous and non-tuberculous meningitis - Shrivastava, Jyotsna; Agrawal, Amit; Patel, Dharmes (International Journal of Medical Research and Review, 2014)
Introduction: Studies have shown the role of cerebrospinal fluid (CSF) adenosine deaminase (ADA) level but simultaneously estimation of serum and CSF-ADA to diagnose tuberculous meningitis (TBM) has been assessed rarely. Therefore, we conducted this study to assess the usefulness of serum and CSF-ADA in diagnosing TBM and to differentiate it with non-tuberculous meningitis in children. Material & Methods: A prospective, case-control study was conducted in tertiary care institution of central India over one year. Children hospitalised with suspected meningitis were recruited and serum and CSF-ADA levels were estimated after dividing them into TBM and non-tuberculous meningitis. Results: Out of 78 recruited cases, 36 had TBM while 42 had non-tuberculous etiology. 32 of 36 TBM cases had CSF-ADA above cut-off value (10U/L) while only 3 out of 42 controls had levels above this. Serum ADA above cut-off (60U/L) was seen in 13 TBM and 2 non-TBM cases. Mean CSF-ADA in cases (18.68±6.21 U/L) was significantly higher than in controls (5.98±2.75 U/L) (p<0.0001); however, serum ADA did not differ significantly between two groups (p=0.0631). CSF-ADA >10U/L showed 92.86% sensitivity and 88.89% specificity (area under ROC curve - 0.9742) in differentiating tuberculous from non-tuberculous meningitis; it also has 91.43% positive predictive value and 90.70% negative predictive value. Serum ADA >60IU/L has shown sensitivity of 95.24% with poor specificity of 33.33%. Conclusion: CSF-ADA estimation is of considerable value to diagnose TBM and to differentiate it from non-tuberculous meningitis but simultaneous estimation of CSF and serum ADA has no additional benefit.